An Impact of Short-Term Climate Oscillations in the Late Pleniglacial and Lateglacial Interstadial on Sedimentary Processes and the Pedogenic Record in Central Poland. (2nd January 2023) - Moska, Piotr; Sokołowski, Robert J.; Zieliński, Paweł; Jary, Zdzisław; Raczyk, Jerzy; Mroczek, Przemysław; Szymak, Agnieszka; Krawczyk, Marcin; Skurzyński, Jacek; Poręba, Grzegorz; Łopuch, Michał; Tudyka, Konrad
Abstract : Environmental studies based on analyses of fluvio-aeolian successions with paleosols in central Poland, forming the central part of the European Sand Belt, are presented. Paleogeographic reconstruction was based on high-resolution analyses of four sites using sedimentological and paleopedological methods as well as forty-four optically stimulated luminescence and fourteen radiocarbon dating measurements. Age-identified individual lithological and soil units were first correlated between sites, emphasizing the differences between them. The results were then correlated with Greenland ice-core stratigraphic units reflecting global environmental changes in the Late Pleniglacial and Lateglacial interstadial, thus ranging from GS-2.1a, through the GI-1 complex (seven subunits), to GS-1. Studies revealed considerable sensitivity of fluvio-aeolian succession to climate changes and oscillations. Climate ameliorations are recorded in fossil soil horizons developed beneath different types of vegetation cover. We detected that the climate cooling GI-1d (the Older Dryas) was not the main phase of dune formation as had been claimed earlier. It is postulated that dunes in the extraglacial zone were formed mainly in GI-1c2 (the Early Allerød). Preexisting dunes were transformed in GS-1 (the Younger Dryas) and in the Early Holocene, locally interrupted by soil formation.